Systematic Literature Review: Development Strategies of Jepara Wood Furniture MSMEs in Indonesia Shariah Economic Review - Raisa Aulia Rahma; Tri Inda Fadhila Rahma; Nurul Jannah (Amkop Management Accounting Review (AMAR), 2025)
Wood furniture Micro, Small and Medium Enterprises (MSMEs) in Jepara play an important role in the regional and national economy. However, this sector faces various challenges, such as global competition, limited capital, market access, and the application of sharia economic principles in business management. This study aims to analyze the development strategy of Jepara wood furniture MSMEs from a sharia economic perspective through a Systematic Literature Review (SLR) approach. The research method uses systematic observation of relevant literature from journals, books, and other academic publications. The results show that the development strategy of wood furniture MSMEs can be done through optimizing sharia-based financing, improving product quality with halal standards, digitizing marketing, and strengthening partnerships with financial institutions and the government. Sharia economic principles, such as justice, transparency, and desirability.